A New Chirp Scaling Algorithm for Highly Squinted Missile-Borne SAR Based on FrFT - Chen, Si; Zhang, Shuning; Zhao, Huichang; Chen, Yong (IEEE journal of selected topics in applied earth observations and remote sensing, 2015)
Since synthetic aperture technology was employed in radar signal processing, a lot of imaging algorithms have been developed for highly squinted synthetic aperture radar (SAR). However, the high-resolution imaging for highly squinted SAR data is still a difficult issue due to the large range migration and strong space-variant characteristic. To accommodate for this problem, a new fractional chirp scaling algorithm (FrCSA) for highly squinted missile-borne SAR is proposed from high resolution point of view in this paper. The performance of the FrCSA is compared to the classical CSA based on fast Fourier transform (FFT). Simulation and real data results indicate that the FrCSA offers better focusing capabilities, greater peak sidelobe ratio (PSLR), and integrated sidelobe ratio (ISLR) by appropriately choosing the rotation angles for the range and azimuth fractional Fourier transform (FrFT).